Effectiveness of the Implementation of the Law on General Provisions and Tax Procedures Related to the Authority of Investigators in Tax Crimes - Rizki, Pebriana; Purnawan, Amin (Jurnal Hukum Khaira Ummah, 2025)
Article 23A of the Constitution of the Republic of Indonesia clearly stipulates that "Taxes and other compulsory levies for state needs are regulated by law." This is the basis that the state is given the authority to carry out compulsory levies but is also limited in that such actions must be regulated in fair and non-arbitrary legal arrangements, so that society does not consider the state to be a thief because it takes people's wealth without the owner's consent. Descriptive research focuses on actual problems and researchers try to synthesize events and incidents that are the center of attention without giving special treatment to the event. Criminal law in criminal acts in the field of taxation has its own specificity, because it needs to be adjusted to the purpose of tax law to put as much money as possible into the state treasury. One of the specific things in criminal acts in the field of taxation is the provisions for investigating criminal acts in the field of taxation carried out by the PPNS of the Directorate General of Taxes. Special arrangements for investigators in criminal acts in the field of taxation are not free from problems, both miscoordination with other law enforcement officers, and the many abuses of absolute investigative authority, which involve criminal acts of corruption in taxation. This encourages renewal in the arrangements investigators of criminal acts in the field of taxation need to be renewed while maintaining the principle of putting as much money as possible into the state treasury.